Carbon Emissions and Governance: Two Sides of the Coin that Determine Corporate Financial Performance - Sisca Santika; Alya Dhiya Atiqah; Hendra Sanjaya Kusno; Tito IM. Rahman Hakim (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Tight business competition encourages public companies to continuously evaluate their performance in order to improve profitability, business sustainability, and financial performance. This evaluation makes carbon emission disclosure increasingly important for investors and the public. This study analyzes the effect of Carbon Emission Disclosure, Board of Directors, and Institutional Ownership on Financial Performance using quantitative methods with 63 data from sustainability and annual reports of mining companies on the IDX for the period 2021-2023. The results show that all three variables simultaneously affect Financial Performance, with Carbon Emission Disclosure having a negative impact, Board of Directors having no effect, and Institutional Ownership having a positive impact.